2013
DOI: 10.3329/bjo.v19i1.12619
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of surgical outcomes of ossiculoplasty using biomaterials and autologous implants

Abstract: Objective: To determine amongst biomaterials (Teflon and Silicon)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Rahul Kawatra et al found no influence of the condition (active or inactive middle ear infection at the time of surgery) on the subsequent graft take rate. (10) Aslam et al found no influence of the state of the middle ear activity on the results of graft take rate ( the take rate was 92.7% in the active ears and 93.1% in the inactive ears). (16) This was not the case in a study done by Sarkar et al ,they found that the percentage of take rate of(164) inactive ears was (91.4%) and( 80.9% ) in active ears.…”
Section: Discussionmentioning
confidence: 97%
“…Rahul Kawatra et al found no influence of the condition (active or inactive middle ear infection at the time of surgery) on the subsequent graft take rate. (10) Aslam et al found no influence of the state of the middle ear activity on the results of graft take rate ( the take rate was 92.7% in the active ears and 93.1% in the inactive ears). (16) This was not the case in a study done by Sarkar et al ,they found that the percentage of take rate of(164) inactive ears was (91.4%) and( 80.9% ) in active ears.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the I‐PORPs responded well at low frequencies but poorly at high frequencies, which may be explained by the relatively higher mass of these prostheses. The lack of any significant difference between the titanium ORPs and the I‐PORP has also been seen clinically, and makes a case for the use of I‐PORPs, because they are autologous tissue and are therefore inherently biocompatible. No significant difference was found between the performance of an I‐PORP contacting the manubrium or the TM, suggesting that this choice should be made based on the specific anatomy of the patient.…”
Section: Discussionmentioning
confidence: 98%